Effect of the Recombinant Human Epidermal Growth Factor Ointment on Cutaneous Surgical Wounds Compared to Antibiotic Ointment - Ryu, Sook In; Kim, Ko Eun; Jeong, Jae Yeong; Park, Jong heon; Moon, Hye-Rim; Kim, Il-Hwan (Annals of dermatology, 2021)
Applying antibiotic ointment after skin surgery can decrease infection and improve scar. Epidermal growth factor (EGF) is known to be able to promote the growth and movement of epidermal cells to stimulate wound healing. Recombinant human EGF (rhEGF) ointment can be used in wet closed dressing to promotes wound healing and prevent complications by maintaining a wet environment. To compare the efficacy of rhEGF ointment and conventional antibiotic ointment after cutaneous resection. Patients who had excision procedures in two or more sites were enrolled. Each wound was assigned to the rhEGF group or the antibiotic ointment group. Wounds were subjected to Physician Global Assessment (PhGA), Patient Global Assessment (PGA), and Patient satisfaction assessment (PSA). The length and area of wounds, and melanin and erythema index (MI and EI) were also assessed for these wounds. Among 11 patients with a total of 20 pairs of resection sites, PhGA, PGA, MI, and EI showed no significant difference between rhEGF and antibiotic ointment groups. However, changes in length and area of wounds showed significant differences between the two groups. RhEGF ointment showed similar short-term cosmetic results with antibiotic ointment, and improved surgical results in regards of the wound size. Applying rhEGF could reduce the use of antibiotic ointments for cutaneous clean (class I) wound surgery.